Analysis and mitigation of the drive train fatigue load for wind turbine with inertial control. (March 2022) - Wang, Yingwei; Guo, Yufeng; Zhang, Dongrui; Liu, Huajun; Song, Rongwu
Highlights: A WT small signal model is established. The impact rules of inertia control on the WT fatigue load of main shaft and tower are revealed. The PI based mitigation control for the drive train fatigue load mitigation is proposed. Abstract: Wind turbine (WT) have attracted more and more attention as a potential way to compensate the fall of the power system inertia by participating in inertial control (IC). However, such inertial control would frequently change the generator torque of the WT according to the system frequency, which increases the fatigue load of the main shaft. However, previous studies have failed to demonstrate a connection between inertia control and WT fatigue load. Thus, this study mainly focuses on the shaft fatigue load caused by inertial control. First, the impact of inertial control on WT fatigue load is analyzed in details. A WT small signal model is established, by which the impact mechanism of inertial control on the shaft torque and tower bending moment could be illustrated. Then, to reduce the impact of inertial control on the WT fatigue load, a PI based mitigation control (PIMC) strategy for the WT fatigue load mitigation is proposed. Simulations in both frequency and time domain are performed to demonstrate the correctness of the proposed method. The results show that the proposed method could greatly reduce the fatigue load of the main shaft while improving the inertia response capacity of the WT.